Pengaruh Patronage Buying Motives Terhadap Prinsip Going Concern Pada UMKM - Chalarce Totanan (Akuisisi: Jurnal Akuntansi, 2018)
This article aims to analyze the influence of patronage buying motives namely of company location, production facility, price, and product quality on going concern principle on UMKM of fried onion in Palu. Respondents in the study were owners or managers of UMKM fried onion industries in Palu, Population 52 based on data from the Industry and Trade Office, but only 40 were active. Data obtained through questionnaires and interviews, processed by SPSS program. Data analysis was done by multiple linear regression. The results, the location of the company and the price did not affect the going concern principle, on the contrary the production facilities and product quality had an effect on going concern principle. Keywords: Patronage Buying Motives, Going Concern, SMEs Onion Fried